Performance Improvement And User Satisfaction Analysis On Android-Based Educational Mobile Game - Anggy Trisnadoli; Kelvin (International ABEC, 2021)
Tourism is a sector currently in the spotlight by many parties, including the government. This is because tourism attracts tourists. Thus tourism can drive the economy and empower the community. However, the lack of promotion from the government and the community makes tourism in Riau Province less well known. Therefore, in 2016 the educational game